Income distribution in less developed countries - Sundrum, R. M. (Routledge, 1992)
This is a major book in a key area of development economics. It gives a comprehensive survey of the link between income distribution and the growth of national income, bringing out major patterns and trends, and concluding that there is still considerable scope for growth with equity in LDCs.